NETWATCH MIKROTIK PADA JARINGAN PT DINASTI KURNIA SEJAHTERA - Taufik Rahman; Alfan Khudori; Hafis Nurdin; Muhammad Qomaruddin (Jusikom : Jurnal Sistem Komputer Musirawas, 2022)
A computer network is of course very much needed by an institution or company to be able to exchange data or do work, especially on the internet network, so not a few companies or institutions have more than one internet subscription to a service provider. However, in reality the rented internet does not automatically replace or switch on the internet that turns off, sometimes you have to move ports and configurations so that trouble occurs when users access the internet and disrupt work. Using netwatch which is a method on the network to avoid connection down time. Used if the company has more than 1 internet source. The way it works is to make the backup of the second line automatically run if the main line dies. However, the problem is when the connection from the ISP (Internet Service Provider) to the internet is interrupted, while the company's MikroTik router can still be connected, so the router will read that there is still a connection and will not change the router's connection to the backup path. By using netwatch which is one of the features of MikroTik, it functions to monitor a host's condition at certain intervals. Netwatch works by periodically sending ICMP messages to the intended host, in this case it can send it to an internet host that is definitely always on. A down connection from the ISP will read down so that the router will automatically change the connection using the backup path.